(untitled) (Bangladesh Journal of Radiology and Imaging, 2026)
We report a rare case of bilateral periventricular nodular heterotopia (PVNH), a congenital brain abnormality resulting from failed neural cell migration associated with disruption of MAP1B and MYH2 genes which are involved in microtubule assembly in neurogenesis. A 1.2 years old girl presented with symptoms of focal seizure since 9 months of age. The patient’s clinical evaluation, in conjunction with CT, MRI brain without contrast and genetic testing, led to the final diagnosis